The effects of acute exercise on long-term episodic memory: a systematic review and meta-analysis - Qazi, Ahmed S.; Schmid, Daphne; Gridley, Nicole; Lambourne, Kate; Daly-Smith, Andrew J.; Tomporowski, Phillip D. (Frontiers in Cognition, 2024)
Research findings reveal a relationship between acute bouts of exercise and procedural/declarative memory. Prior systematic reviews report small/moderate effects of acute exercise on episodic longterm declarative memory. A somewhat overlooked issue is the influence of exercise on specific types of episodic memory processing. The primary focus of this systematic review and meta-analysis was to evaluate the effects of acute bouts of exercise prior to, during, and following encoding on free-, cued-recall, and recognition episodic memory. PubMed, Scopus, and EBSCO databases were entered, and 42 experiments were subject to meta-analysis. Exercise prior to encoding improved memory (d = 0.23) and affected free-recall (d = 0.40) tests of memory more than cued-recall (d = 0.08) or recognition (d = -0.06) memory. Exercise following encoding improved memory (d = 0.33) and affected recognition (d = 0.62) memory more than free-(d = 0.19) or cued-recall (d = 0.14) memory. Exercise during encoding did not influence memory (d = -0.04). Moderator analyses revealed that exercise before encoding impacted memory differentially on the basis of age, exercise type, and test-timing. When exercise occurred after encoding, age and exercise type, but not timing of the test influenced memory performance. Exercise before and after encoding has selective effects on episodic memory. Additional experiments that evaluate how bouts of exercise influence memory encoding are warranted.